Effectiveness of in-game advertising in sports video games among old gamers - Toh, Chee Yong. (2013)
The ways people consume sports have changed over recent years. With more people consuming sports through sports video game (SVG) over watching it on television, the number of in-game advertisements has also increased accordingly. However, studies